2013
DOI: 10.1109/tuffc.2013.2765
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art RF signal generation from optical frequency division

Abstract: We present the design of a novel, ultralow-phase-noise frequency synthesizer implemented with extremely-low-noise regenerative frequency dividers. This synthesizer generates eight outputs, viz. 1.6 GHz, 320 MHz, 160 MHz, 80 MHz, 40 MHz, 20 MHz, 10 MHz and 5 MHz for an 8 GHz input frequency. The residual single-sideband (SSB) phase noises of the synthesizer at 5 and 10 MHz outputs at 1 Hz offset from the carrier are -150 and -145 dBc/Hz, respectively, which are unprecedented phase noise levels. We also report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Finally, the Λ divider implemented with the Max 3000 deserves mentioning for its low noise (b −1 = −130.5 dBrad and b 0 = −165 dBrad 2 /Hz). This is lower than regular dividers (general experience), and just 10 dB above the NIST regenerative dividers [26] at the same output frequency.…”
Section: Measuring the Time Type (X-type) Noise With The λ Dividermentioning
confidence: 70%
See 1 more Smart Citation
“…Finally, the Λ divider implemented with the Max 3000 deserves mentioning for its low noise (b −1 = −130.5 dBrad and b 0 = −165 dBrad 2 /Hz). This is lower than regular dividers (general experience), and just 10 dB above the NIST regenerative dividers [26] at the same output frequency.…”
Section: Measuring the Time Type (X-type) Noise With The λ Dividermentioning
confidence: 70%
“…= 1/2 in n f (t). The mean square slew rate is calculated combining (26) and (27), integrating on frequency, and averaging on θ f . Since sin 2 (θ f ) = 1/2,…”
Section: Input Chattermentioning
confidence: 99%
“…A synthesizer using a time‐base derived via optical frequency division (OFD) offers several technical advantages over architectures based on electronic crystal oscillators. Optical reference cavities exhibit extremely low‐loss and drift and thereby achieve much higher quality factors (Q∼10 11 ) and consequently lower instabilities (10 −16 at 1 s) than room‐temperature electronic resonators .…”
Section: Experimental Section and Methodsmentioning
confidence: 99%
“…Some agility of the microwave comb is possible by tuning the repetition rate of the optical pulse train, but this tends to be slow and limited to 1–2% due to stability constraints of the mode‐locked laser cavity . A combination of OFD and regenerative frequency division can yield RF signals with extremely low‐noise , but this does not enable frequency tuning.…”
Section: Experimental Section and Methodsmentioning
confidence: 99%
“…Kp,03.67.Lx,74.25.nn,85.25.Oj,85.25.Pb Keywords: superconducting, resonator, frequency comb, broadband, RF, microwave Frequency combs in the optical regime have become extremely useful in a wide range of applications including spectroscopy and frequency metrology [1][2][3]. Recently, it was found that a strongly pumped, high-Q optical microcavity made from a nonlinear medium generates sidebands due to a combination of degenerate and nondegenerate four-wave mixing (FWM) [4][5][6] that cascade into a broadband frequency comb of photon energies in the regime of hundreds of THz.…”
mentioning
confidence: 99%